Role of Job Characteristics, Job Promotion and Disciplinary Work In Improving Employee Loyalty Through Job Satisfaction In Department of Public Work in East Java Province - W., Mahmudah Enny (Archives of Business Research, 2016)
Department of Public Work (PU) in East Java Province as one of local government agencies that have a mandate to realize the management of water resources to achieve environmentally sound people’s welfare, and ensure national unity and implemented equitably by relying on participation and community self-reliance. This making human resources as a major component in their duties because no matter how good the technology, if there are not good human resources, the technology will not be able to provide benefits. Therefore, to improve the quality of management attention is expected to pay attention to employee satisfaction climate creates loyalty that will work. This study aims to examine and analyze the effect of job characteristics, promotion and discipline in increasing employee loyalty through job satisfaction at the Department of Public Work in East Java Province. This study uses the independent variables are the characteristics of the job (X1), promotion (X2) and discipline (X3) and the dependent variable is job satisfaction (Y1) and employee loyalty (Y2). Model of the relationship between the variables studied the effect of job characteristics, promotion and discipline in increasing loyalty through satisfaction of employees working there. Characteristics of employment, promotion and discipline have a direct impact on employee loyalty and through job satisfaction. Based on the findings of this study can be used as a policy decision-making and increase the productivity of the employees that are specifically useful for the management of the Department of Public Work in East Java Province.